Factors associated with health and well-being of elders in southern sri lanka - Perera, B.; Wickramarachchi, B.; Thathsarani, D.; Fernando, N. (University of Jaffna, 2012)
The transitions from high to low levels of both mortality and fertility rates, migration and war have induced a significant increase of the proportion of elders in Sri Lanka. Clear understanding of risk and protective factors of health and well being of elders is of utmost importance to make effective public health strategies to combat the adverse consequences of aging in the country. A community survey on a sample of 434 elders was conducted in a southern district to identify factors associated with health and well-being of the aged. The sample consisted of 242 (54.6%) men. The mean age was 70.8 years (SD=8.2). About 36 of the respondents had only primary level education or no formal education. Half of the respondents were in the poor income category. Over all, the proportion of widows among the elderly is higher than that of widowers. Diabetes (20%), hypertension (32%), arthritis (52%), Asthma (18%), visual defects (63%) and memory loss (30%) were the most prevalent physical and psychological illnesses reported by the respondents. Elders face difficulties in obtaining health care and other public services available in the country. Elders in urban areas were more vulnerable than their rural counterparts to experience economical hardships. About 64% of elderly men living in rural areas and about 55% of elderly men living in urban areas were current alcohol users. About 25% of elderly men living in urban and about 23% of elderly men living in rural areas were current smokers. The majority of elders (about 90%) were physically active. About 80% of the respondents reported having had good social support. Aging has become a serious public health issue in Sri Lanka. Promotion of healthy life style behaviors, upgrading and expanding geriatric health care services in the country, searching avenues to establish a social security system for the elderly and taking necessary actions to maintain and to enhance the existing social support system available for elders would assist the elderly in Sri Lanka to age successfully.
Keywords: Aging; Health; Sri lanka